Distribution of weather elements and its influence on crops in the north region of Rio Grande do Sul state and the extreme west of the Santa Catarina state, Brazil - Caron, Braulio Otomar; Behling, Alexandre; Schmidt, Denise; Nardini, Claiton (Revista Brasileira de Climatologia, 2024)
Knowledge on the behavior of the meteorological elements of a region is of great importance for decision making, especially in agricultural cultivation, as they will directly influence the growth and development of crops. Therefore, the objective of this work was to know the distribution of meteorological elements by the nonparametric Kernel distribution and to analyze their influence on the cultivation of crops. The study was conducted using data obtained from the Automatic Weather Station A854-Frederico Westphalen. The station is located in the municipality of Frederico Westphalen, Rio Grande do Sul, Brazil. The meteorological elements used in the study were the incident global solar radiation, rainfall and average air temperature. The data were organized as overall, per year and per month. Nonparametric kernel density estimation method was used. The application of nonparametric Kernel density estimation method to the meteorological elements allowed us to observe the distribution over the 10 years of record overall, in the year and in the month. Furthermore, the distribution made it possible to identify the highest peaks that are related to higher densities. The observation of 10 years of records of solar radiation, rainfall and air temperature data from the weather station by the nonparametric Kernel distribution method gives an indication of how the elements are presenting themselves in the period. Despite specific restrictions, the weather/climate is suitable for the cultivation of species that have been used in the region, following their zoning.